Differences in cortical coding of heat evoked pain beyond the perceived intensity: An fMRI and EEG study. Issue 4 (1st March 2013) - Haefeli, Jenny; Freund, Patrick; Kramer, John L.K.; Blum, Julia; Luechinger, Roger; Curt, Armin
<x xml:space="preserve">Abstract</x> Imaging studies have identified a wide network of brain areas activated by nociceptive stimuli and revealed differences in somatotopic representation of highly distinct stimulation sites (foot vs. hand) in the primary (S1) and secondary (S2) somatosensory cortices. Somatotopic organization between adjacent dermatomes and differences in cortical coding of similarly perceived nociceptive stimulation are less well studied. Here, cortical processing following contact heat nociceptive stimulation of cervical (C4, C6, and C8) and trunk (T10) dermatomes were recorded in 20 healthy subjects using functional magnetic resonance imaging (fMRI) and electroencephalography (EEG). Stimulation of T10 compared with the C6 and C8 revealed significant higher response intensity in the left S1 (contralateral) and the right S2 (ipsilateral) even when the perceived pain was equal between stimulation sites. Accordingly, contact heat evoked potentials following stimulation of T10 showed significantly higher N2P2 amplitudes compared to C6 and C8. Adjacent dermatomes did not reveal a distinct somatotopical representation. Within the assessed cervical and trunk dermatomes, nociceptive cortical processing to heat differs significantly in magnitude even when controlling for pain perception. This study provides evidence that controlling for pain perception is not sufficient to compare directly the magnitude of cortical processing [blood oxygen level dependence (BOLD) response and amplitude of evoked potentials] between body sites. Hum Brain Mapp 35:1379–1389, 2014. © 2013 Wiley Periodicals, Inc.